Results of the Multi-Domain Task-Completion Dialog Challenge - Li, Jinchao; Peng, Baolin; Lee, Sungjin; Gao, Jianfeng; Takanobu, Ryuichi; Zhu, Qi; Minlie Huang; Schulz, Hannes; Atkinson, Adam; Adada, Mahmoud (Proceedings of the 34th AAAI Conference on Artificial Intelligence, Eighth Dialog System Technology Challenge Workshop, 2020)
The paper provides an overview of the “Multi-domain Task Completion” track (Track 1) at the 8th Dialog System Technology Challenge (DSTC-8). There are two tasks in this track. The first task is end-to-end multi-domain task-completion, which aims to build end-to-end task completion dialog systems based on ConvLab. The second task is fast domain adaptation, seeking to develop models that predict user responses when only limited in-domain data is available. We describe the submissions for both tasks, automatic evaluation and human evaluation procedures, and discuss the outcomes of these two evaluations.